A mini‐review of microstructural control during composite fiber spinning. Issue 5 (20th January 2022) - Xu, Weiheng; Jambhulkar, Sayli; Ravichandran, Dharneedar; Zhu, Yuxiang; Lanke, Shantanu; Bawareth, Mohammed; Song, Kenan
Abstract: From wool to Kevlar, one‐dimensional (1D) fiber has experienced the transition from clothing materials to structural applications in the past centuries. However, the recent advancements in tooling engineering and manufacturing processes have attracted much attention from both academia and industry to fabricate novel, versatile fibers with unique microstructures and unprecedented properties. This mini‐review focuses on the fabrication techniques of porous, coaxial, layer‐by‐layer and segmented fibers with continuous solution and melt fiber spinning methods. In each section of this review article, the unique structure‐related applications, including intelligent devices, healthcare devices, energy storage systems, wearable electronics and sustainable products, are discussed and evaluated. Finally, the combination of additive manufacturing for 1D fiber patterning in two‐dimensional and three‐dimensional devices, in addition to challenges in the reviewed fiber microstructures, is briefly introduced in the conclusion. © 2021 Society of Industrial Chemistry. Abstract : Review on solution spinning and melt spinning based porous, coaxial, layer‐by‐layer and segmented fiber microstructures and applications.